2020
DOI: 10.1002/job.2481
|View full text |Cite
|
Sign up to set email alerts
|

Seeking and finding justice: Why and when managers' feedback seeking enhances justice enactment

Abstract: Summary There is growing recognition that justice enactment is a complex activity and that managers face significant contextual and situational roadblocks when attempting to enact justice. However, research has not fully examined how managers, in the course of their jobs, can (a) identify and respond to justice‐related issues and (b) assemble and synthesize relevant information required to act in a manner consistent with justice rules. To begin addressing these concerns, we posit feedback seeking as a key mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…They create community by recognizing both group accomplishments, and individual contributions to the team's success. Taken together, the specific behaviors reflected in these five practices help leaders to motivate and inspire followers toward cooperation (Kouzes and Posner 2017), and have been used extensively in prior research (e.g., Burkman et al 2019;Caza and Posner 2019;Hage and Posner 2015;Kouzes and Posner 2019;Sherf et al 2020).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…They create community by recognizing both group accomplishments, and individual contributions to the team's success. Taken together, the specific behaviors reflected in these five practices help leaders to motivate and inspire followers toward cooperation (Kouzes and Posner 2017), and have been used extensively in prior research (e.g., Burkman et al 2019;Caza and Posner 2019;Hage and Posner 2015;Kouzes and Posner 2019;Sherf et al 2020).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…First, justice agents may inadvertently be unfair because of informational asymmetry, which may make them simply unaware of the impact and interpretation of their decisions and behavior. Sherf and colleagues (2021) discuss the complexity of justice judgments and enactment, in particular the need to “assemble and synthesize relevant information required to act in a manner consistent with justice rules.” Feedback seeking, as Sherf and colleagues (2021) demonstrate, is thus an important practice in the justice enactment process.…”
Section: Uncharted Waters: Critical Reflections and Future Directionsmentioning
confidence: 99%
“…Two of the papers focus on cognitive foundations of justice enactment and specifically on how construal level influences the delivery of bad news (Holt, Bobocel, & Chen, 2021) and punishment of misconduct (van Houwelingen, van Dijke, van Hiel, & de Cremer, 2021). Two other papers highlight justice enactment as a joint process between managers and employees; one highlighting the role of upward feedback (Sherf, Gajendran, & Posner, 2021) and one the role of managers' gender in how their overall fairness is judged by employees (Varty, Barclay, & Brady, 2021). Two further papers lead us to consider the issue of power in the context of justice enactment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy involves the perceived belief that one is capable of a specific behavior (Williams, 2010) and has been associated with greater effort, engagement, and performance (Avolio & Hannah, 2008;Judge & Bono, 2001). A recent study showed that managers with higher levels of self-efficacy in their job reported that they enacted more distributive, procedural, and informational justice towards their employees than those managers who reported less self-efficacy (Sherf et al, 2020).…”
Section: The Role Of Abilitymentioning
confidence: 99%